A Modified Fanger’s Model for Malaysia Climate - J. S., Pau; K. K., Kee; William, K. S Pao (ENCON 2013, 2013)
Thermal comfort is the condition of mind, which expresses satisfaction with the thermal environment. The unwavering need to have thermal comfort in tropical climate has caused excessive use of air conditioning, resulting in the issue of energy over-consumption. One of the solutions is to run air conditioners at the minimal energy level to reduce wastage. There are two approaches in thermal comfort research, namely the deterministic engineering approach which is based on Fanger’s heat balance model and the person-environment architectural approach, which is collectively called the Adaptive Method. Adaptive Method has slowly been accepted in the thermal comfort research as it regards humans as an adaptive being that is dynamic in nature and has the ability to adjust to environmental changes. This research aims to integrate adaptive theories into Fanger’s model to widen the application of Fanger’s model in tropical countries, particularly in Malaysia. The research has proposed the limitation of PMV to ±1.3 for 80% occupant satisfaction, with an increment of ±0.3 from the original limitation of PMV as in ASHRAE Standard. The increment provides tolerance to adaptive mechanism and dynamic fluctuations of thermal preferences of subjects in tropical countries. It is verified that the new adaptive Fanger’s model is applicable in Malaysian HVAC and NV buildings.